Conservation Priorities of NTFP Species in Dry Deciduous Forests of Adilabad District, Telangana, India - Kanneboyena, Omkar; Suthari, Sateesh; Ragan, A.; Raju, Vatsavaya S. (Our Nature, 2015)
Non-Timber Forest Products (NTFPs) have been used by ethnic and non-ethnic people for their food, shelter, medicine and commerce in Adilabad district of Northern Telangana. Over exploitation of the products has reduced the economic plant taxa and led to the loss of plant species which are essential for ecosystem diversity. The availability and distribution of the 16 NTFP species studied are not uniform in the district as per the phytosociological study. They are prioritized into three categories on the basis of score attained in the devised scale. Among these, Firmiana simplex, Givotia mulaccana, and Aegle marmelos shall receive the highest conservation priority, followed by Madhuca longifolia var. latifolia, Dendrocalamus strictus at moderate level while Terminalia bellerica, Syzygium cumini and Tamarindus indica are of low category which do not require much conservation attempt. Our Nature (2015), 13(1): 1-7